2007
DOI: 10.1186/1476-069x-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Are liver and renal lesions in East Greenland polar bears (Ursus maritimus) associated with high mercury levels?

Abstract: Background: In the Arctic, polar bears (Ursus maritimus) bio-accumulate mercury as they prey on polluted ringed seals (Phoca hispida) and bearded seals (Erignathus barbatus). Studies have shown that polar bears from East Greenland are among the most mercury polluted species in the Arctic. It is unknown whether these levels are toxic to liver and kidney tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 30 publications
3
29
0
3
Order By: Relevance
“…For example, high Hg concentrations of 61 μg/g ww in the liver of Atlantic bottlenose dolphins (Tursiops truncatus) were associated with liver abnormalities (Rawson et al, 1993). The histopathological changes found in the liver of Arctic marine mammals (i.e., Arctic beluga, polar bear, bowhead whale, pilot whale and ringed seal) are similar to those observed in other Hg-exposed marine and laboratory mammals (Woshner, 2000;Woshner et al, 2002;Sonne et al, 2007Sonne et al, , 2010. The latter, however, showed that histopathological changes could also be ascribed to age and dietary composition 0.01 0.1 1 10 100 1000 10000 ww Eastern Beaufort Sea, Canada, 1991 (age adjusted 6.9 years) Southwest Melville Island, Canada, 1991 (age adjusted 6.9 years) Cumberland Peninsula, Canada, 1991 (age adjusted 6.9 years) Cape Mercy, Canada, 1991 (age adjusted 6.9 years) Avanersuaq (north), Greenland, 1988-90 (age 2-6 years) Avanersuaq (north), Greenland, 1988-90 (age >6 years) Avanersuaq (south), Greenland, 1988-90 (age 1 year) Avanersuaq (south), Greenland, 1988-90 (age 2-6 years) Avanersuaq (south), Greenland, 1988-90 (age >6 years) Ittoqqortoormiit, Greenland, 1999 (all ages) Ittoqqortoormiit, Greenland, 1999 (adult male) Ittoqqortoormiit, Greenland, 1999 (adult female) Ittoqqortoormiit, Greenland, 1999 Ittoqqortoormiit (north), Greenland, 1983-90 (age 1 year) Ittoqqortoormiit (north), Greenland, 1983-90 (age 2-6 years) Ittoqqortoormiit (north), Greenland, 1983-90 (age >6 years) Ittoqqortoormiit (south), Greenland, 1983-90 (age <1 year) Ittoqqortoormiit (south), Greenland, 1983-90 (age 2-6 years) Ittoqqortoormiit (south), Greenland, 1983-90 (age >6 years) Fig.…”
Section: Liver Exposure and Effectssupporting
confidence: 52%
See 2 more Smart Citations
“…For example, high Hg concentrations of 61 μg/g ww in the liver of Atlantic bottlenose dolphins (Tursiops truncatus) were associated with liver abnormalities (Rawson et al, 1993). The histopathological changes found in the liver of Arctic marine mammals (i.e., Arctic beluga, polar bear, bowhead whale, pilot whale and ringed seal) are similar to those observed in other Hg-exposed marine and laboratory mammals (Woshner, 2000;Woshner et al, 2002;Sonne et al, 2007Sonne et al, , 2010. The latter, however, showed that histopathological changes could also be ascribed to age and dietary composition 0.01 0.1 1 10 100 1000 10000 ww Eastern Beaufort Sea, Canada, 1991 (age adjusted 6.9 years) Southwest Melville Island, Canada, 1991 (age adjusted 6.9 years) Cumberland Peninsula, Canada, 1991 (age adjusted 6.9 years) Cape Mercy, Canada, 1991 (age adjusted 6.9 years) Avanersuaq (north), Greenland, 1988-90 (age 2-6 years) Avanersuaq (north), Greenland, 1988-90 (age >6 years) Avanersuaq (south), Greenland, 1988-90 (age 1 year) Avanersuaq (south), Greenland, 1988-90 (age 2-6 years) Avanersuaq (south), Greenland, 1988-90 (age >6 years) Ittoqqortoormiit, Greenland, 1999 (all ages) Ittoqqortoormiit, Greenland, 1999 (adult male) Ittoqqortoormiit, Greenland, 1999 (adult female) Ittoqqortoormiit, Greenland, 1999 Ittoqqortoormiit (north), Greenland, 1983-90 (age 1 year) Ittoqqortoormiit (north), Greenland, 1983-90 (age 2-6 years) Ittoqqortoormiit (north), Greenland, 1983-90 (age >6 years) Ittoqqortoormiit (south), Greenland, 1983-90 (age <1 year) Ittoqqortoormiit (south), Greenland, 1983-90 (age 2-6 years) Ittoqqortoormiit (south), Greenland, 1983-90 (age >6 years) Fig.…”
Section: Liver Exposure and Effectssupporting
confidence: 52%
“…Kidney lesions have been reported in whale species and polar bears from the Arctic (cf. Woshner, 2000;Woshner et al, 2002;Sonne et al, 2007Sonne et al, , 2010Rosa et al, 2008) resemble those reported for gray seals (Halichoerus grypus) and ringed seals and bottlenose dolphins living in the heavily metal and organohalogen polluted regions such as the Baltic Sea (Lavery et al, 2009;Bergman et al, 2001). However, some work has shown that age and micro-pathogens (e.g., bacteria and parasites) are important co-factors in the development of kidney lesions in Arctic marine mammals which must be considered when evaluating metal toxicosis (Woshner, 2000;Woshner et al, 2002;Sonne et al, 2007Sonne et al, , 2010Rosa et al, 2008).…”
Section: Renal Exposure and Effectsmentioning
confidence: 62%
See 1 more Smart Citation
“…These lesions are uncommon in cetaceans (Howard, 1983;Gulland et al, 2001); however, they have been reported in other marine mammals such as pinnipeds (Bergman et al, 2001) and polar bears (Ursus maritimus) (Sonne et al, 2006(Sonne et al, , 2007. In polar bears, these lesions are often associated with exposure to organohalogenated compounds and mercury; these pollutants are immunosuppressive and favour recurrent infections after which immune complex deposition occurs (Sonne et al, 2006(Sonne et al, , 2007. In addition to the deposits on the glomerular basement membrane, cases with a membranoproliferative reaction presented with marked glomerular hypercellularity of mesangial cells.…”
Section: Discussionmentioning
confidence: 95%
“…Embora já relatado na literatura, o potencial fibrótico do Hg no tecido renal não foi estudado em profundidade (ETO, et al, 1997;SONNE, et al, 2007;SLEEMAN, et al, 2010). Por exemplo, na insuficiência renal aguda induzida por tratamento com cloreto de Hg em ratos, notáveis depósitos de fibronectina nos rins foram encontrados (SABALL, et al, 2001).…”
Section: Timerosal Altera a Transição De Permeabilidade Mitocondrial unclassified